Economic problems of land management (Journal of actual problems of jurisprudence, 2023)
The article considers the economic problems of land management in Kazakhstan. As one of the most land-based States in the world, agriculture contributes little to economic growth. Serious land-use violations continue to be identified through a number of State audits or no land use at all. The aim of the study is to highlight the economic problems of land administration. The study identified a number of economic aspects and problems that affect the effectiveness of land administration. It is noted that the proportion of private land ownership varies by region. The level of rent has an impact on the efficiency of land use. The current level of rent is unreasonable and does not motivate the land user to manage the land. In urban areas, the purpose of the site is not taken into account in the initial land valuation. The lack of regulation of the market for environmental products and infrastructure from accreditation agencies discourages land users from adopting more environmentally friendly approaches to land-based agriculture. Key words: land resources, land use problems, agriculture, land leasing, soil quality, land administration, land tax, land valuation, land sale, land fund, ecology, efficiency.